Korean Wave: Strategi Pelaku Industri di Korea dalam Menghadapi Tantangan di Tengah Pandemi Covid-19 - Ahnaf Hananda Naufal Rafif; Rahel Yuanita; Tiara Permatasari (Andalas Institute of International Studies, 2022)
K-pop industry players remain active in making new innovations in the face of new and unexpected problems. Like globalization which involves almost everyone in the world who is influenced or influenced in today's global relations. The Covid-19 pandemic has disrupted the entire world without exception, all aspects are affected by Covid-19. Various activities must be carried out virtually, including k-pop music concerts which are usually synonymous with fan cheering activities, but must also be turned into virtual concerts which result in limitations in our activities or in feeling the sensation of enjoying concerts. What is the strategy of the actors driving the Korean wave in facing challenges during the Covid-19 pandemic? By using the library research method, we found that during the pandemic, industry players who play a role in the Korean Wave phenomenon, have their own way of maintaining the existence of the Korean Wave during the pandemic, namely by making new innovations such as holding virtual K-Pop concerts, marketing products with e-commerce, and utilizing the Korean entertainment industry in introducing Korean specialties